Engaged Reading as a Collaborative Transformative Practice. (September 2015) - Ivey, Gay; Johnston, Peter H.
The context of this study is a voluntary modification in teaching focus by four eighth-grade teachers who shifted their instructional focus toward student engagement. They abandoned assigned readings in favor of student-selected, self-paced reading within a collection of high interest materials—primarily young adult fiction that students found personally relevant. Over a 4 year period, among other things, this shift consistently resulted, for the students, in increased reading volume, a reduction in students failing the state test, and changes in peer relationships, self-regulation, and conceptions of self. Increasingly predictable shifts across classes in the nature of classroom activity systems along with increasingly predictable student-level outcomes have been accompanied by a parallel evolutionary shift in the activity of teaching (individually and collectively) among the four teachers, reflected in their relationships, their use of resources, and the objects of their activity. Using Cultural Historical Activity Theory (CHAT), we analyze this co-evolution of activity systems and the subjectivities and development of individuals acting within those systems. We examine the inseparable shifts in community and individual activity, and their evolution over three time scales—a 4 year history of change in practice among a small community of teachers, the evolution of their student communities over the course of a school year, and, at the microgenetic level, the moment-to-moment interactional processes that feed the evolution of individuals and the relational properties of their communities.